(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The reformed pension system in the Republic of North Macedonia has created an interest based on three poles: legal, financial and social. Therefore, the paper aims to provide not only overview of the North Macedonian pension legislative, the model of financing of the reformed pension system but also to take into account the social character of the pension system. Following the basic European values and the interception of the EC recommendations that were underline in the last 10 years for North Macedonia, the country remains moderately prepared in this area. The rapidly increased expenditure on pensions and the efforts to improve the legal, institutional and social framework on the North Macedonian pension system became new burden for the Public Pension Fund. Therefore, the sustainability and the efficiency of the contemporary pension system is under question mark. This paper will explore the major challenges and opportunities that were foster by the new pension reforms from the reconstructed pension system. The one-pillared based system (Pay As You Go system– based on principle of generation solidarity,) has become system based on three pillars (fully funded mandatory pension insurance and fully funded voluntary pension insurance). Regarding the legal and financial aspects of the reformed pension system, there will be three areas of research emphasis: delayed transfer of funds from the state pension insurance fund to private funds, the procedures for supervising voluntary pension insurance schemes and the limits on investing in non-domestic securities. These three aspects resulted in a breach of the legislation on the management of deposits in Republic of North Macedonia, and they were not in line with the acquis under Financial Services Chapter that consists mostly of legal arrangements concerning with capital markets, insurance (including individual pension systems) and banking sectors. This is why they found their place in the annual reports (for 2015, 2016 and 2018) of the European Commission on the Republic of North Macedonia in negative connotation. Analysis of the legislation, as well as comparing the legislation with EU recommendation, is expected to answer the question if our country is complying with the recommendations. The paper will be based on a legal, comparative, analytical and synthetic method that will provide a multidisciplinary approach in acquiring knowledge and in delivering results that will be of relevance to all involved stakeholders (future pensioners, pension funds, central and decentralized government).